ANAEROBIC PERFORMANCE OF PRE-PUBERTAL GIRLS AND ADULT WOMEN ON CYCLE-ERGOMETER AND BLOOD AMMONIA AND LACTATE CONCENTRATIONS (Fiep Bulletin - online, 2015)
The purpose of the present study was to compare performance of pre-pubertal girls and adult women during a 15 seconds all-out effort on cycle-ergometer and the maximal post-exercise blood lactate (La) and ammonia (NH3) concentrations. 24 female subjects were investigated (12 girls and 12 women), with an average age of 9,7  0,9 e 22,4  3,3 years, respectively. Girls were classified as Tanner's stage 1 for maturation of secondary sexual characteristics. First, body height, body mass, lean body mass and percent fat were assessed. Then, all subjects carried out a maximal exercise on cycle-ergometer during 15 seconds. Peak power (Ppeak) and mean power (Pmean) were continuously measured during exercise. Peak and mean power relative to body mass were then calculated. Blood samples were taken for determination of lactate and ammonia concentrations. Peak power (270,3  28,3W; 8,3  0,9 W/kg for the girls and 595,9  59,3W; 10,8  0,6 W/kg for the women) and mean power (228,0  26,5W; 7,0  0,9W/kg for the girls and 503,8  49,1W; 9,1  0,4W/kg for the women),  were significantly different between the groups. La 1 min (girls = 6,8  2,0 mmol/L and women = 8,0  1,3 mmol/L) was not different between girls and women. However, La 3min (girls = 6,2  1,6mmol/L and women = 9,1  1,3mmol/L) and NH3 (girls = 140,8  58,6 g/dL and women = 249,4  42,0 g/dL) were significantly higher in women. These results suggest that anaerobic performance is higher in adult women and that these differences can not be caused by different muscle mass or body dimensions. The higher capacity to generate anaerobic energy during high intensity, short-duration exercises in adult women may be associated to higher performance in this group.
Keywords: lactate; ammonia; maximal effort